Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas dan Rasio Likuiditas pada PT Hutama Karya (Persero) Periode 2015-2024 (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the financial performance of PT Hutama Karya (Persero) for the period 2015–2024 using profitability and liquidity ratios. The method used is descriptive qualitative research with data collection techniques through documentation of financial reports. Profitability ratios are measured by Net Profit Margin (NPM) and Return on Assets (ROA), while liquidity ratios are measured by Current Ratio and Quick Ratio. The results show that the profitability performance of PT Hutama Karya experienced fluctuations but showed a significant improvement since 2021. Similarly, liquidity ratios that were below industry standards during the 2015–2020 period showed improvements during the 2021–2024 period. Overall, the company shows a positive trend in financial management during the final period of the study. These findings are expected to serve as a reference in financial decision-making and asset management strategies in the future.